Biphasic Chromatin Structure and FISH Signals Reflect Intranuclear Order - Jyoti P. Chaudhuri; Eva Kasprzycki; Mathew Battaglia; John R. McGill; Anton Brøgger; Joachim-U. Walther; Albrecht Reith (Cellular Oncology)
Background and Aim: One of the two parental allelic genes may selectively be expressed, regulated by imprinting, X-inactivation or by other less known mechanisms. This study aims to reflect on such genetic mechanisms. Materials and Methods: Slides from short term cultures or direct smears of blood, bone marrow and amniotic fluids were hybridized with FISH probes singly, combined or sequentially. Two to three hundred cells were examined from each preparation. Results and Aignificance: A small number of cells (up to about 5%), more frequent in leukemia cases, showed the twin features: (1) nuclei with biphasic chromatin, one part decondensed and the other condensed; and (2) homologous FISH signals distributed equitably in those two regions. The biphasic chromatin structure with equitable distribution of the homologous FISH signals may correspond to the two sets of chromosomes, supporting observations on ploidywise intranuclear order. The decondensed chromatin may relate to enhanced transcriptions or advanced replications. Conclusions: Transcriptions of only one of the two parental genomes cause allelic exclusion. Genomes may switch with alternating monoallelic expression of biallelic genes as an efficient genetic mechanism. If genomes fail to switch, allelic exclusion may lead to malignancy. Similarly, a genome-wide monoallelic replication may tilt the balance of heterozygosity resulting in aneusomy, initiating early events in malignant transformation and in predicting cancer mortality.